Pengaruh Variasi Konsentrasi Kuning Telur terhadap Abnormalitas Sperma Puntius bramoides Pascakriopreservasi 48 Jam - Pertiwi, Primasari; Abinawanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The study aims to determine the effect of several concentrations of egg yolk as an effective natural cryoprotectant for cryopreservation and to analyze the quality of spermatozoa of Puntius bramoides fish (lukas fish) 48 hours after cryopreservation. This study used a Completely Randomized Design (CRD) with 9 treatments and 4 replications. The concentrations of egg yolk used as cryoprotectants were 0% (negative control), 5%, 7%, 9%, 11%, 13%, 15%, 17%, and the use of Carboxymethyl Cellulose (CMC) 1% as a positive control. The results showed that the use of several concentrations of egg yolk as a natural extracellular cryoprotectant was able to significantly affect (P <0.005) the abnormalities of spermatozoa of lukas fish 48 hours after cryopreservation. The use of 9% egg yolk concentration is the optimum concentration in reducing the percentage of abnormality of sperm in lukas fish with an average percentage obtained of 26.13 ± 1.49%.